2014
DOI: 10.1021/nn5012144
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Stable Hydrogen Evolution Electrocatalysts Based on Molybdenum Compounds on Carbon Nanotube–Graphene Hybrid Support

Abstract: Highly active and stable electrocatalysts for hydrogen evolution have been developed on the basis of molybdenum compounds (Mo2C, Mo2N, and MoS2) on carbon nanotube (CNT)-graphene hybrid support via a modified urea-glass route. By a simple modification of synthetic variables, the final phases are easily controlled from carbide, nitride to sulfide with homogeneous dispersion of nanocrystals on the CNT-graphene support. Among the prepared catalysts, Mo2C/CNT-graphene shows the highest activity for hydrogen evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
356
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(370 citation statements)
references
References 48 publications
11
356
0
3
Order By: Relevance
“…As expected, the Pt/C electrode is highly active toward HER, demonstrating comparable activity to that as reported in literature 25, 28. As expected, the bulk‐phase WN electrode showed rather poor HER activity, as indicated by a large initial overpotential ( U onset ) of 331 mV and large overpotential of 492 mV at the representative current density of 10 mA cm −2 (η 10 ), respectively, which can be explained by its low number of active sites, poor electronic conductivity, and nonoptimized surface properties.…”
supporting
confidence: 88%
“…As expected, the Pt/C electrode is highly active toward HER, demonstrating comparable activity to that as reported in literature 25, 28. As expected, the bulk‐phase WN electrode showed rather poor HER activity, as indicated by a large initial overpotential ( U onset ) of 331 mV and large overpotential of 492 mV at the representative current density of 10 mA cm −2 (η 10 ), respectively, which can be explained by its low number of active sites, poor electronic conductivity, and nonoptimized surface properties.…”
supporting
confidence: 88%
“…MoS2 grown over CNFs and MoS2-synthesized produced about 374 and 98 times higher current density at −0.30 V (vs. RHE) compared with the MoS2-commercial sample, respectively. Youn et al have reported an overpotential of 255 mV for MoS2 synthesized on carbon nanotube -graphene hybrid support at 10 mA/cm 2 [41].…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al have synthesized monolayer of MoS2 quantum dots and observed a Tafel slope of 59 mV/decade [45]. MoS2 grown on Toray paper, MWCNT, and CNT/graphene showed a Tafel slope of 120, 109 and 100 mV/decade, respectively [41,46,47]. Some important parameters for MoS2 based HER catalysts are given in Table S1 for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Pt‐based materials have been proven to be the most efficient electrocatalysts for hydrogen evolution reaction (HER), the high cost, limited supply, and poor durability hinder their global‐scale application 3, 4. Therefore, much effort has been dedicated to develop robust nonnoble‐metal HER catalysts,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 such as cobalt‐, nickel‐, iron‐, tungsten‐, and molybdenum‐based materials.…”
mentioning
confidence: 99%